Badminton Players’ Moral Intentions: A Factorial Survey Study Into Personal and Contextual Determinants - De Waegeneer, Els; Constandt, Bram; Van Der Hoeven, Stef; Willem, Annick (Frontiers in Psychology, 2019)
Improving and maintaining high ethical standards among athletes is a major challenge in sports, which requires sufficient knowledge on athletes’ moral intentions. This study advances our knowledge on athletes’ moral intentions by examining the personal and contextual determinants (factors) that influence moral intentions of badminton players. In a factorial survey study, a total of 171 participants were asked to respond to scenarios describing moral dilemmas in the context of badminton. This approach allows combining advantages from both classical experiments and survey methods, enabling the determination of the underlying principles of the judgments and intentions of respondents. Multilevel analysis indicated that intention to engage in the described behaviour was impacted by both the act and the gender of the subject. This study complements previous research on athletes’ moral intentions by the advanced method of factorial survey, while supporting the development of more specific approaches in the promotion of ethical behaviour in sports.